Copper and lead levels in two popular leafy vegetables grown around Morogoro Municipality, Tanzania - Chove, BE; Ballegu, WR; Chove, LM (Tanzania Journal of Health Research, 2006)
A study was carried out to determine the levels of two heavy metals, Lead (Pb) and Copper (Cu), in two popular leafy vegetables grown around Morogoro Municipality in Tanzania. Vegetable samples of Pumpkin leaves ( Cucurbita moschata) and Chinese cabbage ( Brassica chinensis) were collected from three sites and analysed for their concentrations of the two metals using an Atomic Absorption Spectrophotometer. The three sites, namely Mazimbu, Kihonda and Towelo are located within a 10 km perimeter. The site selection was based on the anticipated levels of contamination of the water used for irrigation. The results showed that the levels (mg/100g dry weight) ranged from 0.885 to1.39 for Copper and 0.05 to 0.315 for Lead. The levels of Lead and Copper varied between the vegetable varieties and from site to site. Vegetables from Mazimbu showed higher concentration levels of the two metals compared to the other sites in both varieties. Towelo vegetables had relatively low concentrations. There was a significant difference (P<0.05) in levels of the two metals across the sites but there was no significant difference (P>0.05) in the levels of Copper between the two vegetable varieties from all the three sites. There was a significant difference (P<0.05) in the levels of Lead between the vegetable varieties. The levels of both Lead and Copper in the two vegetables were found to be below the maximum permissible levels recommended by FAO/WHO for the two metals in vegetables. Keywords: Brassica chinensis, Cucurbita moschata, copper, lead, vegetables, Tanzania Tanzania Health Research Bulletin Vol. 8(1) 2006: 37-40